Evaluation of Using Slag Powder as a Filler for Asphalt Concrete - Hussein, Zainab M.; Mohamedmeki, Mohammed Z.; Al-Mumaiz, Maha (Salehan Institute of Higher Education, 2025)
Filler materials have a significant effect on the performance of asphalt concrete by filling the voids and modifying the binder viscosity. Many types of filler have been used; the Ordinary Portland Cement (OPC) is the most used due to its properties, which align with the required properties. The cost, production emissions, and drain for natural resources formed negative points of its usage. Accordingly, this study is dedicated to evaluating the asphalt concrete properties using byproduct material as a mineral filler. The Electric Arc Furnace Slag Powder (EAFSP) has been selected to replace the OPC with ratios from zero to 100% with an increment of 25%. Marshall and Indirect Tensile Strength (ITS) results in different testing conditions were employed to evaluate the use of EAFSP. The results revealed that using EAFSP as a filler material improved asphalt concrete strength and resistance to moisture effects, especially at high temperatures. More binder content was needed, about 0.6%, the voids in the total mix were reduced by about 1%, and the stiffness increased by about 0.5 kn/mm when replacing the OPC with EAFSP. Based on that, it's recommended that the replacement ratio should be proposed according to the weather condition, materials availability, and cost-benefit analysis.